Ovarian hyperstimulation: modern tactics of managing patients - Yu E Dobrokhotova; E I Borovkova (IP Berlin A.V., 2017)
The article presents current data on ovarian hyperstimulation syndrome. Classification, criteria for assessing the severity and in algorithmic form, see diagnostic and treat-ment approach to patients management. Separately theis sues of prevention of thromboembolic complications.